El control patrimonial y su relación con la administración de bienes muebles de la UGEL Padre Abad de Ucayali, año 2022 - Romero Martin, Dina Ruth (2023)
The objective of this research was to determine the relationship between patrimonial control and the administration of personal property of the UGEL Padre Abad de Ucayali, year 2022. The research methodology included a basic type, correlational and non-experimental design, probabilistic sampling, population of 50 workers of the UGEL Padre Abad de Ucayali, from the areas of logistics, supply, planning or other administrative areas, as well as a sample of 45 actors of such population group. The most important results showed that the patrimonial control over the movable assets of the UGEL Padre Abad de Ucayali evidences the understanding of aspects such as additions arising from a legal disposition, retirements arising from technical obsolescence, but also the non-consideration of additions arising from an arbitration and judicial mandate, administrative acts, acts of registration, etc. Likewise, it was reflected that the administration of the movable assets of the UGEL Padre Abad de Ucayali, object of patrimonial control, must attend to planning based on the definition of programs, generation of coherence, organization based on a principle of unity, etc. Finally, the main conclusion was that there is a significant relationship between patrimonial control and the administration of movable assets of the UGEL Padre Abad de Ucayali, being this conclusion consistent with Spearman's correlation standard 0.993, obtained for the general working hypothesis.